The WTO and the Poorest Countries : The Stark Reality - Mattoo, Aaditya (IMF Working Papers; Working Paper ;, 2004)
Small and poor countries pose a challenge for the World Trade Organization (WTO). These countries have acquired a significant say in WTO decision-making. However, they have limited ability to engage in the reciprocity game that is at the heart of the WTO, and have limited interests in the broader liberalization agenda because of their preferential access to industrial country markets. Accommodating the interests of the small and poor countries is desirable in itself, but would also facilitate expeditious progress in the Doha Round. The stark reality facing the system is that the desirable ways of addressing their concerns- providing them additional financial assistance and nonpreferential market access-is proving infeasible. As a result, the system is gravitating toward the less desirable option of relieving these countries of obligations, including those that might be welfare-enhancing for them.